AKTIVITAS BIOLOGI DARI SENYAWA TERPENOIDS SOFT CORAL GENUS SINULARIA sp - M Janib Achmad; Nebuchadnezzar Akbar (Prosiding Seminar Nasional Kemaritiman dan Sumber Daya Pulau-Pulau Kecil, 2017)
The soft coral genus Sinularia is one of the most widely distributed soft corals. It constitutes a dominant portion of the biomass in the tropical reef environment. Sinularia elaborates a rich harvest of secondary metabolites including sesquiterpenes, diterpenes, polyhydroxylated steroids, and polyamine compounds. These metabolites were recently shown to possess a range of biological activities such as antimicrobial, anti-inflammatory, and cytotoxic activities. During the past decade, Sinularia has yielded many new structures with novel skeletons. Several of the previously published secondary metabolites have been reexamined for their pharmacological properties, and the results strongly support further investigations. The current article reviews the terpenoids of the soft coral genus Sinularia and their pharmacological significance.Keywords: Marine natural products, Soft corals,, Octocorals, Sinularia, Bioactive terpenes, Terpenoids.